Engagement, Authenticity, and Advocacy in "Youth Uncensored": Ethics in Applied Theater Research With Street-Involved Youth. (February 2023) - Conrad, Diane
"Youth Uncensored" was an applied theater project with youth affiliated with an arts-based, nonprofit organization serving street-involved youth. The organization identified the need to educate service providers about the youth's experiences to better meet youth's needs. The youth were involved in all aspects of the process of creating workshops for service providers, from generating content for our scenes to devising, rehearsing, and performing scenes for service provider audiences, and participating in forum theater activations, in talk-back sessions, and in evaluating the project. For an evaluation of outcomes for youth, the youth created a 30-min video exploring the projects' benefits and challenges. Through a close reading of the video, this article addresses the ethical issues that arose in relation to engagement, authenticity, and advocacy. Our ongoing efforts at negotiating this ethical terrain were crucial for the endurance and efficacy of the project.